Left atrial strain as a pre-operative prognostic marker for patients with severe mitral regurgitation. (1st February 2021) - Mandoli, Giulia Elena; Pastore, Maria Concetta; Benfari, Giovanni; Bisleri, Gianluigi; Maccherini, Massimo; Lisi, Gianfranco; Cameli, Paolo; Lisi, Matteo; Dokollari, Aleksandr; Carrucola, Chiara; Vigna, Mariangela; Montesi, Gianfranco; et al.
Abstract: Background: In patients with severe mitral regurgitation (MR), additional echocardiographic indices could be helpful to optimize surgical timing before irreversible left heart myocardial dysfunction has occurred. We investigated the correlation of left atrial (LA) strain by speckle tracking echocardiography with prognosis after mitral surgery for severe MR, and its association with LA fibrosis. Method: 71 patients with primary severe MR undergoing pre-operative echocardiographic assessment were initially enrolled. Exclusion criteria were: other valvular disease>moderate, history of coronary artery disease, heart failure (HF), hypertrophic cardiomyopathy, left bundle branch block, previous pacemaker implantation, heart transplantation, poor acoustic window. The primary endpoint was the occurrence of composite events (HF and mortality); the secondary endpoint was post-operative functional capacity (NYHA and Borg CR10 class). LA fibrosis was assessed by atrial biopsy specimens in a subset of patients. Results: Of 65 eligible patients, the primary endpoint occurred in 30 patients (medium follow-up: 3.7 ± 1 years for event-group, 6.8 ± 1 years for non-event group). After Kaplan-Meier analysis, peak atrial longitudinal strain (PALS) provided good risk stratification (5-year event-free survival:90 ± 5% for PALS≥21% vs 30 ± 9% for PALS<21%, p   <   0.0001 ); it was an independent and incremental predictor of outcome in four multivariate Cox adjusted models. There was also an association between PALS and the secondary endpoint (NYHA: r 2  = 0.11, p   =   0.04; Borg CR10: r 2  = 0.10, p   =   0.02 ) and an inverse correlation between PALS<21% and LA fibrosis (r 2 0.80, fibrosis: 76.6 ± 20.7% vs 31.9 ± 20.8%; p   <   0.0001 ). Conclusions: Global PALS emerged as a reliable predictor of outcome and functional capacity for severe primary MR, and as a marker of LA fibrosis. Highlights: In severe mitral regurgitation (MR), optimal surgical timing should be recognized. Preoperative left atrial strain could be useful to assess prognosis after MR surgery. LA reservoir strain was a good predictor of clinical and functional outcome in MR. LA reservoir strain was also correlated with LA fibrosis assessed by atrial biopsy.